International multicenter validation of GES score for HCC risk stratification in chronic hepatitis C patients. Issue 9 (24th June 2022) - Shiha, Gamal; Soliman, Reham; Mikhail, Nabiel N. H.; Carrat, Fabrice; Azzi, Jessica; Nathalie, Ganne‐Carrié; Toyoda, Hidenori; Uojima, Haruki; Nozaki, Akito; Takaguchi, Koichi; Hiraoka, Atsushi; Atsukawa, Masanori; et al.
Abstract: We have recently demonstrated the ability of a simple predictive model (GES) score to determine the risk of hepatocellular carcinoma (HCC) after using direct‐acting antivirals. However, our results were restricted to Egyptian patients with hepatitis C virus (HCV) genotype 4. Therefore, we studied a large, independent cohort of multiethnic populations through our international collaborative activity. Depending on their GES scores, patients are stratified into low risk (≤ 6/12.5), intermediate risk (> 6–7.5/12.5), and high risk (> 7.5/12.5) for HCC. A total of 12, 038 patients with chronic HCV were analyzed in this study, of whom 11, 202 were recruited from 54 centers in France, Japan, India, the U.S., and Spain, and the remaining 836 were selected from the Gilead‐sponsored randomized controlled trial conducted across the U.S., Europe, Canada, and Australia. Descriptive statistics and log‐rank tests. The performance of the GES score was evaluated using Harrell's C‐index (HCI). The GES score proved successful at stratifying all patients into 3 risk groups, namely low‐risk, intermediate‐risk, and high‐risk. It also displayed significant predictive value for HCC development in all participants ( p < .0001), with HCI ranging from 0.55 to 0.76 among all cohorts after adjusting for HCV genotypes and patient ethnicities. The GES score can be used to stratify HCV patients into 3 categories of risk for HCC, namely low‐risk, intermediate‐risk, and high‐risk, irrespective of their ethnicities or HCV genotypes. This international multicenter validation may allow the use of GES score in individualized HCC risk‐based surveillance programs.